2005
DOI: 10.1097/01.ju.0000165386.26542.23
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Associations of Urogenital Pain and Sexual Function in a Community Based Cohort of Older Men: Olmsted County, Minnesota

Abstract: Urogenital pain may be associated with impaired sexual function in older men. Furthermore, men with impaired mental health may be less likely to report pain associated impairment of sexual function, while the reverse may be true in the presence of comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
2
14
0
1
Order By: Relevance
“…Lutz et al (2005) reported that, after adjustment for age, the cross-sectional associations of urogenital pain and sexual function were evaluated in a community-based cohort in older men, and that with a regular sexual partner there were significant associations of testicular pain with impaired sexual drive and satisfaction. In a controlled clinical trial study on 770 men performed in Germany, sexual dysfunction was found to have been more frequently reported by men with pelvic pain than by men without a pain syndrome (Beutel, Weidner, & Brahler, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lutz et al (2005) reported that, after adjustment for age, the cross-sectional associations of urogenital pain and sexual function were evaluated in a community-based cohort in older men, and that with a regular sexual partner there were significant associations of testicular pain with impaired sexual drive and satisfaction. In a controlled clinical trial study on 770 men performed in Germany, sexual dysfunction was found to have been more frequently reported by men with pelvic pain than by men without a pain syndrome (Beutel, Weidner, & Brahler, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…This questionnaire is readily self-administered in research or clinical settings, and has become the gold standard inventory for the assessment of sexual function (Rosen et al, 1997). Most data suggest that chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and urogenital pain impair the overall quality of life, leading to sexual dysfunction (Lutz et al, 2005;Müller & Mulhall, 2005;Sadeghi-Nejad & Seftel, 2006). These observations led us to conduct a prospective study to investigate the influence of CSP on sexual function and these reports have focused on the adverse effects of orchialgia on the quality of life, with consequent indirect effects on sexuality.…”
Section: Introductionmentioning
confidence: 99%
“…Lutz et al (2005) found that testicular pain impairs sex drive and satisfaction and perineal pain increases patients' sexual problems. In another study, pain has been associated with sexual anxiety, lack of interest in sex, and orgasm and erectile difficulties, although without bacterial testing, it cannot be ruled out that organic pathology is causing both the pain and sexual dysfunction (Pitts, Ferris, Smith, Shelley, & Richters, 2008).…”
Section: Painmentioning
confidence: 97%
“…Une autre étude fait état de sensations douloureuses chez 1,5 % de 2115 patients [15]. Une analyse de la douleur urogénitale par Lutz et al [16] met en évidence une prévalence de 1,4 % chez les hommes âgés de 40 à 49 ans, et de 1,8 % chez les patients âgés de 50 à 59 ans. Nickel et al signalent en revanche une prévalence beaucoup plus élevée à 9,7 % chez les hommes âgés entre 20 et 74 ans [17].…”
Section: Incidenceunclassified